Analysis of the Impact of PSAK 72 Implementation on Company Performance at PT Telkom Indonesia (Persero) Tbk - Wahyuni; A.Megawati Junaedi; Dinda; Arya Saputra Syam; Andry Ilyas (Masterpiece, 2026)
This study aims to analyze the impact of PSAK 72 implementation on the financial performance of PT Telkom Indonesia (Persero) Tbk by comparing financial conditions before and after the adoption of the revenue recognition standard. A quantitative approach with a comparative time-series design was employed using secondary data obtained from the company’s audited annual financial statements for 2017–2022. The observation period was divided into two phases: the pre-PSAK 72 period (2017–2019) and the post-PSAK 72 period (2020–2022). Financial performance was evaluated using the Current Ratio (CR) to measure liquidity and the Net Profit Margin (NPM) to assess profitability. The results show that the average CR decreased from 90% before PSAK 72 implementation to 78% after implementation, representing a 12 percentage-point decline. In contrast, the average NPM increased from 15% to 16%, indicating a 1 percentage-point improvement in profitability. These findings indicate that PSAK 72 implementation was accompanied by changes in the company’s liquidity and profitability performance. The decline in liquidity may reflect changes in the recognition and presentation of contract-related assets and liabilities, while the improvement in profitability suggests that the company maintained its ability to generate net income despite changes in revenue recognition. The study contributes empirical evidence regarding the financial implications of PSAK 72 implementation in the telecommunications industry.